Fetih Derneği ve İstanbul’un Fethinin 500. Yılı / Association of Conquest and The 500th Anniversary of Conquest of Istanbul - Tağmat, Çağla Derya (Journal of History Culture and Art Research, 2015)
Fetih Derneği ve İstanbul’un Fethinin 500. Yılı Öz Türkiye’de, 500. yıldönümü 1953 yılında kutlanacak olan İstanbul’un Fethi kutlamaları için hazırlıklara Cumhurbaşkanı İsmet İnönü döneminde başlanmış ve 1950 yılında 500. Yıl ve Müteakip Fetih Yıllarını Kutlama Derneği adıyla bir dernek kurulmuştur. 1950 yılında yapılan seçimler sonucunda yaşanan hükümet değişimi fetih kutlama planlarına gölge düşürmemiş ve hazırlıklar devam etmiştir. Demokrat Parti iktidarı döneminde hazırlıklarına hızlı bir şekilde devam eden cemiyet, yaşadığı maddi imkânsızlıklara rağmen çeşitli faaliyetler organize etmiştir. Başbakan Adnan Menderes ve Cumhurbaşkanı Celal Bayar’ın katılmadığı kutlama etkinlikleri, çeşitli eksiklikler ve devlet erkânının katılmamasından dolayı basın tarafından sert eleştirilere maruz kalmıştır. Diğer yandan devlet erkânının törenlere katılmamış olması kutlanılan olayın bir diğer muhatabı Yunanistan tarafından da bir sağduyu örneği olarak nitelendirilmiştir. Bu çalışmada, Demokrat Parti döneminde faaliyet gösteren Fetih Derneği, derneğin yapısı, organizasyonları ve kutlama faaliyetleri arşiv belgeleri ve süreli yayınlar kullanılarak incelenmiştir. Association of Conquest and The 500th Anniversary of Conquest of Istanbul Abstract In Turkey, the preperations of conquest celebrations of Istanbul, of which 500th anniversary would be celebrated in 1953, were begun in the period of President Ismet Inonu and an association called Association of 500th Anniversary and Celebrating the Following Anniversaries of Conquest of Istanbul was founded. The governmental change as a result of 1950 elections did not overshadow to the plans of conquest celebrations and then preparations continued. The association which proceeded its preparations rapidly in the Democratic Party era, organised several activities inspite of financial impossibilities. The celebration activities in which Prime Minister Adnan Menderes and President Celal Bayar didn’t attend were criticised rigorously by press because of the deficiencies of organizations and absence of high officials. On the other hand the absence of the president and the prime minister in the celebrations, was qualified as an example of common sense by the other part of the case, Greece. In this study the Association of Conquest which was active in Democrat Party era, the structure and organizations of the association and its celebration activities were analysed in the light of archival documents and periodicals.